The juvenile courts an overall view / Zainon Mahat - Mahat, Zainon (Faculty of Law, 1986)
Among the Malaysian public, there exists an ignorance of the existence of a special court in dealing with juvenile offenders. Most people think that these juvenile offenders are dealt by the same court that deals with adult offenders. This ignorance should not go unchecked. Therefore the purpose of my writing this paper is to make known to the public, the 'behind-the-scenes' of a Juvenile Court. To achieve a more realistic understanding of this topic, I have make special references to the Kuala Lumpur Juvenile Court, the welfare Department of Wilayah Persekutuan and other relevant authorities which deals with juvenile problems. The thread of analysis of this paper will touch on the practice and procedure adopted by the Juvenile Court from the time a child or a young person is apprehended by the police until his case is determined by the court, acting in pursuant to the provisions of the Juvenile Courts Act, 1947.